New PLA/ZnO:Cu/Ag bionanocomposites for food packaging - C. Vasile; M. Rapa; M. Stefan; M. Stan; S. Macavei; R. N. Darie-Nita; L. Barbu-Tudoran; D. C. Vodnar; E. E. Popa; R. Stefan; G. Borodi; M. Brebu (eXPRESS Polymer Letters)
Plasticized poly(lactic acid) (PLA) samples with embedded Cu-doped ZnO powder functionalized with Ag nanoparticles composites were prepared by melt blending processing technique. The effect of ZnO:Cu/Ag nanoparticles on the properties of plasticized PLA was investigated in terms of structural (by Attenuated total reflectance – Fourier Transform Infrared – ATR-FT-IR, X–Ray Diffraction analysis – XRD) and morphological (using Scanning Electron Microscopy – SEM and Transmission Electron Microscopy – TEM examination) modifications, thermal (Differential Scanning Calorimetry – DSC), mechanical (transmittance, tensile strength), barrier antimicrobial properties and also in respect to migration of Cu, Zn an Ag nanoparticles into food simulants. It was found that the increase of nanoparticle content (from 0.5 to 1.5 wt%) of PLA formulations leads to the increase of the degree of crystallinity of PLA. The overall migration of all samples into three food simulants was below 10 mg·dm–2, accepted value according to EU Regulation No 10/2011 for plastic materials and articles intended to come into contact with food. Based on the obtained results it can conclude that the optimum composition is PLA/ZnO:Cu/Ag 0.5, this bionanocomposite offering suitable mechanical and thermal properties, good barrier properties to ultraviolet light, water vapour, oxygen and carbon dioxide, antibacterial activity and low migration amount of nanoparticles into food simulants.